Analisis Kebijakan Kartu Tenaga Kerja Luar Negeri (KTKLN) Bagi TKI Re-Entry Jawa Tengah Sebagai Bentuk Perlindungan Terhadap Buruh Migran Indonesia - Khoeriyah, Asrofiyatul; ., Sulistyowati; Astuti, Puji (Journal of Politic and Government Studies, 2014)
This research aims to describe the policy of Overseas Worker’s ID Card (KTKLN) for TKI Re-Entry in Central Java as a form of protection for Indonesian migrant workers. KTKLN is a policy issued has mandated by UU No. 39/2004 on The Protection and Placement of Indonesian Workers Aboard (PPTKILN) in providing protection to migrant workers and insurance data covered in the form of a smartcard. However, the implementation of KTKLN are implemented effectively for all migrant workers in 2011. Before 2010 KTKLN only applied to new migrant workers, for TKI Re-Entry not required to have KTKLN as a condition for departure. This raises several problems that can be assessed from KTKLN’s policy as to how the implementation of policies implemented since the regulation of KTKLN in 2004 to be implemented effectively in 2010? How roles and functions held by KTKLN in providing protection against TKI Re-Entry? And what are the barriers faced by migrant workers in the Re-Entry KTKLN-making document handling? As well as the expectations of the workersrelated to with re-entry issues and obstacles experienced in the administration ofKTKLN.In this research , the researcher used qualitative approach that will generatedescriptive data. This study took a sample of the policies implemented in Central JavaProvince, to obtain the appropriate data source research goals, the researcher usespurposive sampling technique by conducting interviews with BP3TKI Central Java,Director General of Immigration I Semarang, NGO / LBH, TKI Re-Entry, StaffManpower and Transmigration Ministry and PPTKIS in Central Java. In addition,researchers also observe and study the document to increase the information inanalyzing of the data acquired.